Penerapan ILO Convention Nomor 111 Ke dalam Undang-Undang Ketenagakerjaan Di Indonesia - Murni, Layla; HZ, Evi Deliana; Diana, Ledy (PATTIMURA Legal Journal, 2022)
Introduction: Discrimination in employment and occupation through the Law of the Republic of Indonesia Number 21 of 1999 concerning Ratification of the ILO Convention No. 111 Concerning Discrimination In Respect Of Employment And Occupation by implementing it in Article 5 of Law Number 13 of 2003 concerning Employment. However, Article 5 Law 13 of 2003 concerning Manpower have not specifically defined discrimination so that there is still discrimination against job seekers in company job vacancies. Purposes of the Research: To find out how the implementation of ILO Convention No. 111 into the Indonesian Manpower Act regarding legal protection for job seekers from discriminatory work requirements and find out what Indonesia's policies are after ratifying ILO Convention No. 111. Methods of the Research: The type of research used is normative legal research, namely using literature studies in searching the data. Results Originality of the Research: The results showed the application of the ILO Convention No. into the Indonesian Manpower Law regarding Legal Protection for Job Seekers. Indonesia's labor regulations are still not specific in terms of discrimination in the field of employment, so it is necessary to make more detailed and specific rules regarding this matter which can later become a clear legal basis in terms of discrimination in the field of employment and protect the rights of Indonesian job seekers.